1999
DOI: 10.1109/63.737609
|View full text |Cite
|
Sign up to set email alerts
|

Sensorless torque control of salient-pole synchronous motor at zero-speed operation

Abstract: A position and speed sensorless control using the counter electromotive force of permanent-magnet motor (PM) debases the control performance at a low speed. We will propose a controllable system at full speed, including a zero speed using saliency.At low speed, the sensorless control is made by observing a current ripple at a time when alternating voltage has been applied to a salient-pole motor. Also, for discriminating the S and N poles of the magnet, magnetic saturation is used. A device has been applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(80 citation statements)
references
References 5 publications
0
80
0
Order By: Relevance
“…• Transient signal injection based schemes which exploit the PWM signal in order to extract the rotor position or to inject discrete test voltage pulses in a defined direction (Raute et al, 2007;Belie et al, 2010;Vogelsberger et al, 2010) • Continuous high frequency signal injection based schemes which consist on injection of signal reported to a rotating high frequency voltage vector in the stator reference frame (α,β), (Perassi et al, 2005;Hu et al, 2008) or injection of signal reported to a pulsating high frequency voltage vector in a reference frame (d,q) synchronous with the motor saliency (Aihara et al, 1999;Sakamoto et al, 2001;Holtz, 2008;Wiedmann et al, 2009;Kock et al, 2009) Transient signal injection schemes are very complex to be implemented for practical real time systems whereas continuous high frequency signal injection schemes are based on a simple excitation and are easier to be experimentally implemented. However, continuous HFSI technique performance and robustness depend on the parameters choice of the high frequency signal injected in order to extract the rotor position or the rotor position error (Taniguchi et al, 2007).…”
Section: Fig 1: Pmsm Sensorless Control Techniques Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…• Transient signal injection based schemes which exploit the PWM signal in order to extract the rotor position or to inject discrete test voltage pulses in a defined direction (Raute et al, 2007;Belie et al, 2010;Vogelsberger et al, 2010) • Continuous high frequency signal injection based schemes which consist on injection of signal reported to a rotating high frequency voltage vector in the stator reference frame (α,β), (Perassi et al, 2005;Hu et al, 2008) or injection of signal reported to a pulsating high frequency voltage vector in a reference frame (d,q) synchronous with the motor saliency (Aihara et al, 1999;Sakamoto et al, 2001;Holtz, 2008;Wiedmann et al, 2009;Kock et al, 2009) Transient signal injection schemes are very complex to be implemented for practical real time systems whereas continuous high frequency signal injection schemes are based on a simple excitation and are easier to be experimentally implemented. However, continuous HFSI technique performance and robustness depend on the parameters choice of the high frequency signal injected in order to extract the rotor position or the rotor position error (Taniguchi et al, 2007).…”
Section: Fig 1: Pmsm Sensorless Control Techniques Classificationmentioning
confidence: 99%
“…As the HFSI method consists in injecting a high frequency voltage on the d-axis rotor voltage, it causes magnetic saliency excitation (Aihara et al, 1999;Sakamoto et al, 2001). Then, the HFSI results in high frequency voltage and current components and in an error rotor position ∆θ e defined as Eq.…”
Section: High Frequency Pmsm Modelmentioning
confidence: 99%
“…In the case of field-strengthening, motor reluctance increases due to magnetic saturation. Hence, we can specify the magnet polarity by measuring the increase in motor reluctance (2) (3) . From (8) and (9), following high frequency current amplitude I p is defined.…”
Section: Magnetic Polarity Detectionmentioning
confidence: 99%
“…MODELING [2]- [4]. Hence, it is common to employ a hybrid a L R 0 i 1+1 dw Idt (1) sensorless technique, which uses both a signal injection based b IIs i method and a back-EMF based method [5]. Back-EMF based LvC 0 0 RS icL dVfcldt sensorless methods were first developed to estimate the rotor where va, vb, vc ia, ib, ic, V1a, Vib and are the 3-phase voltages, position of BLAC motors having a surface-mounted PM rotor currents, and flux-linkages, respectively, and Rs is the phase without rotor magnetic saliency.…”
Section: Introduction Is Demonstrated Experimentally In Section IVmentioning
confidence: 99%
“…back-EMF based sensorless schemes [2]- [5]. The modeling of Clearly, qI/d, fqi dqdid/t and dfqiqdt vary non-linearly with the dq-axis cross-coupling magnetic saturation, the investigation of d-and q-axis currents, due to the influence of magnetic its influence on the accuracy of the rotor position estimation in saturation.…”
Section: Introduction Is Demonstrated Experimentally In Section IVmentioning
confidence: 99%